Long term application of bus monitoring system to short and medium span bridges and damage detection - Miyamoto, Ayaho (2018)
In this study, as one solution to the problem for condition assessment of existing short and medium span reinforced/prestressed concrete bridges, a new monitoring method using a public bus as part of a public transit system (bus monitoring system) is proposed, along with safety indices, namely, characteristic deflection, which is relatively free from the influence of dynamic disturbances due to such factors as the roughness of the road surface, and a structural anomaly parameter. A basic study was conducted by using the results of technical verification experiments and numerical analysis simulation. This paper describes the details of not only how to assess the bridge condition by public bus vibration measured in operating on Ube City bus network as a specific example for verify the system but also what kind of consideration we need to apply the system to existing bridges in overseas country.